Diseño del Sistema de Control para un Sincronizador Automático, Integrado a la Red Electrica de Smurfit Kappa Colombia (2018)
Smurfit Kappa Colombia (SKC) located in Yumbo, has seen the need to make technological innovations in order to be more competitive on its environment, due to the high standards managed in the paper industry both nationally and internationally. As a result, the company must have a high reliability in its main energy sources to guarantee the availability for the most possible number of hours – days. For this, it has been identified in the electric grid of the company that exists the difficulty of reconnecting safely and quickly to the Regional Interconnect System (SIR) after an event has forced the plant to operate isolated (out of the external grid). This causes great disturbances in the production, as some internal plants stop its operation because the company's own power supply does not cover the demand required to keep operational the entire plant. To solve this, we propose the design of the control for an automatic synchronizer that integrates the analogous, discrete and control variables for the generator and the involved energy bars, to carry out an effective and safe synchronism in less time, by controlling the conditions in which the generator should be in order to regulate its speed and voltage to match the conditions of the external grid.